PKM : Pelatihan Berbasis Komunitas Meningkatkan Keterampilan Teknis Masyarakat Desa - Fadhil Muhmammad Basysyar; Cep Lukman Rohmat; Ahmad Rifa’i; Rilanisa Zhahiran Herlambang; Najwa Tuzzahra (CV. Multi Kreasi Media, 2024)
The Community Service Program (PKM) is designed to enhance the technical skills of village communities through community-based training. This training aims to empower village residents with practical skills that can improve their productivity and well-being. In the context of rapid economic and technological changes, technical skills are crucial for the success and sustainability of local businesses. Village communities face challenges in acquiring relevant and up-to-date technical skills. The lack of access to practical training and information about the latest technologies hinders their ability to adopt more efficient work methods and improve the quality of their products. This contributes to low competitiveness and limited economic opportunities. The objectives of the program include enhancing technical skills by providing comprehensive training in technology and relevant practical skills to improve productivity and work quality, and empowering local communities by building their capacity to manage and apply new skills in their businesses, thus enhancing economic opportunities and overall quality of life. The implementation methods involve planning and preparation through community surveys, forming an implementation team, and developing training materials that align with local needs; conducting training sessions that include both theory and practice, focusing on technical skills such as tool usage, new technologies, and efficient work methods, with training conducted directly in the village to facilitate access; and providing post-training guidance to help participants apply the skills acquired and conducting periodic evaluations to assess the training's effectiveness and impact on productivity. The results of community-based training show significant enhancement of technical skills among village residents. Before the training, only a small portion of the community had adequate technical skills, but after the training, skill levels increased sharply. Participants showed improved abilities in using tools and new technologies, as well as applying more efficient work methods. Additionally, there were positive impacts on productivity and product quality, and increased economic opportunities for the village community. This training also strengthened the sense of community and collaboration among participants, building a strong foundation for long-term sustainability.